The Human Right to a Worthy Life as a Legal Concept - KOBYLINSKY, Svetlana V. (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The relevance of the research problem is caused by the modern discourse of human rights protection. The research investigates the legal aspects of the concepts of ‘adequate’ and ‘worthy’ living standards in the context of the fundamental principle of activity of a modern democratic state, which is guaranteed by Part 1 of Article 7 of the Constitution of the Russian Federation. The comparative legal analysis of national and international regulatory legal acts demonstrated the effectiveness of legal regulation of human rights. In addition, the research investigated the connection between the material level and moral standards established by ideas and values of life. Thus, the submissions can serve as a basis for the improvement of the regulatory legal framework in rights and freedoms protection.